GTPase Networks in Membrane Traffic - Mizuno-Yamasaki, Emi (2012)
Members of the Rab or ARF/Sar branches of the Ras GTPase super-family regulate almost every step of intracellular membrane traffic. A rapidly growing body of evidence indicates that these GTPases do not act as lone agents but are networked to one another through a variety of mechanisms to coordinate the individual events of one stage of transport and to link together the different stages of an entire transport pathway. These mechanisms include guanine nucleotide exchange factor (GEF) cascades, GTPase-activating protein (GAP) cascades, effectors that bind to multiple GTPases, and positive-feedback loops generated by exchange factor-effector interactions. Together these mechanisms can lead to an ordered series of transitions from one GTPase to the next. As each GTPase recruits a unique set of effectors, these transitions help to define changes in the functionality of the membrane compartments with which they are associated.